2019
DOI: 10.1021/acs.inorgchem.9b00319
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of U(VI) with BiPDA, DmBiPDA, and PhenDA: Comparison on Structures and Binding Strengths in Aqueous and DMSO/20%(v)H2O Solutions

Abstract: The stability constants (log β) of 1:1 uranyl complexes with three N,O-mixed donor ligands (L = 2,2′-dipyridyl-6,6′-dicarboxylate, 3,3′-dimethyl-2,2′-bipyridine-6,6′-dicarboxylate, and 1,10-phenanthroline-2,9-dicarboxylate, denoted as BiPDA, DmBiPDA, and PhenDA, respectively) in aqueous and DMSO/​20%(v)­H2O solutions were determined by spectrophotometry in 0.1 M tetraethylammonium perchlorate. The effects of ligand preorganization, steric hindrance, and solvation on the binding strength of U­(VI) with the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…In our previous work, we investigated the complexation thermodynamics of BiPDA and PhenDA with U­(VI) as well as PhenDA with Np­(V) in solutions. In the present work, the stability constants and the enthalpy of the complexation between lanthanides (Nd and Eu) and N , N ,­ N ′, N ′-tetramethyl-2,2′-bipyridine-6,6′-dicarboxamide (TMBiPDA) and N , N ,­ N ′, N ′-tetramethyl-1,10-phenanthroline-2,9-dicarboxamide (TMPhenDA) in CH 3 OH/​10%(v)­H 2 O solutions were determined by thermodynamic measurements including spectrophotometry and microcalorimetry.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we investigated the complexation thermodynamics of BiPDA and PhenDA with U­(VI) as well as PhenDA with Np­(V) in solutions. In the present work, the stability constants and the enthalpy of the complexation between lanthanides (Nd and Eu) and N , N ,­ N ′, N ′-tetramethyl-2,2′-bipyridine-6,6′-dicarboxamide (TMBiPDA) and N , N ,­ N ′, N ′-tetramethyl-1,10-phenanthroline-2,9-dicarboxamide (TMPhenDA) in CH 3 OH/​10%(v)­H 2 O solutions were determined by thermodynamic measurements including spectrophotometry and microcalorimetry.…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, the complexation mechanisms of PDA (L 1 ) with [UO 2 (CO 3 ) 3 ] 4− and H 2 VO 4 − , HVO 4 2− have been systematically studied by density functional theory (DFT). To explore the effect of the ligand backbone on the extraction behavior, two analogous tetradentate N,O-mixed donor ligands [2,2′-bipyridine]-6,6′-dicarboxylate acid 31,32 (L 2 ) and 5 H -cyclopenta[2,1- b :3,4- b ′]dipyridine-2,8-dicarboxylate acid 33,34 (L 3 ) were also investigated for comparative analysis (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Following Hard-Soft-Acid-Base (HSAB) concept, it may be advisable to choose macrocyclic ligands with hard oxygen donor center for cation like U(VI), however, the extensive presence of lanthanides and other alkali metals within the nuclear waste often throws competition toward the efficiency of actinide extraction. Therefore, significant studies [19][20][21] have been devoted on exploring how other alternative donor center such as 'N', 'S' or mixed-donor center (N,O) based ligands perform in chelation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of lanthanides and other alkali metals in large excess within the nuclear waste often adversely affects actinide extraction. Therefore, significant studies have been devoted to exploring how other alternative donor centers such as N, S, or mixed-donor center (N, O)-based ligands perform in chelation. Undoubtedly, the availability of sophisticated quantum-mechanical techniques such as density functional theory (DFT) and advancement of tools that utilize the orbital- and density-based information played a significant role in understanding the actinide complexation with macrocycles in depth. , Theoretical investigations on uranyl complexes with variants of hexaphyrin ligands indicated that the change in size and shape of a ligand cavity modulates the ionic/covalent character of metal–ligand bonds and subsequently alters the binding affinities …”
Section: Introductionmentioning
confidence: 99%